2022
DOI: 10.1038/s41536-022-00266-z
|View full text |Cite
|
Sign up to set email alerts
|

Strategies to capitalize on cell spheroid therapeutic potential for tissue repair and disease modeling

Abstract: Cell therapies offer a tailorable, personalized treatment for use in tissue engineering to address defects arising from trauma, inefficient wound repair, or congenital malformation. However, most cell therapies have achieved limited success to date. Typically injected in solution as monodispersed cells, transplanted cells exhibit rapid cell death or insufficient retention at the site, thereby limiting their intended effects to only a few days. Spheroids, which are dense, three-dimensional (3D) aggregates of ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
39
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 160 publications
0
39
0
Order By: Relevance
“…Spheroid diameter regulates nutrient availability to the aggregate core due to gradients within the spheroid and can have important implications on spheroid function. 10,43 We did not observe differences in the spheroid metabolic activity with diameters below 250 μm. However, previous studies demonstrated that smaller mesenchymal stromal cell (MSC) spheroids exhibit higher levels of proliferation and metabolic activity due to greater nutrient availability, while slightly larger spheroids can secrete higher levels of trophic factors.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…Spheroid diameter regulates nutrient availability to the aggregate core due to gradients within the spheroid and can have important implications on spheroid function. 10,43 We did not observe differences in the spheroid metabolic activity with diameters below 250 μm. However, previous studies demonstrated that smaller mesenchymal stromal cell (MSC) spheroids exhibit higher levels of proliferation and metabolic activity due to greater nutrient availability, while slightly larger spheroids can secrete higher levels of trophic factors.…”
Section: Discussionmentioning
confidence: 59%
“…Spheroids are dense cellular aggregates that are promising building blocks for tissue engineering due to their increased cell–cell interactions, upregulated cytokine production, retention of endogenous ECM, as well as enhanced cell survival in vitro and in vivo compared to monodisperse cells. , Spheroids have been fabricated from a variety of cell types, ,, yet literature on skeletal muscle spheroids is sparse . Aggregation of muscle cells into spheroids has largely focused on understanding the behavior of primary muscle cells, but the application of this approach in tissue engineering lags behind other tissue types such as bone, , cardiac, and adipose, , among others.…”
Section: Introductionmentioning
confidence: 99%
“…The use of spheroids is currently under investigation for many cell types. To improve the therapeutic effect of cell spheroids even further, various biomaterials (e.g., fibers and hydrogels) have been developed for spheroid engineering [ 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 ]. Note that hydrogels, as artificial 3D cell scaffolds, have attracted great attention in recent years because of their ability to reproduce the biological environment, with their inherent biochemical and physicochemical properties, such as cell adhesion, degradation, and viscoelasticity ( Figure 1 ) [ 1 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, techniques based on this method require specialized training, resulting in a lack of reproducible results. In addition, the formed spheroids pose challenges in immunostaining, imaging, retrieval, and storage. , …”
Section: Introductionmentioning
confidence: 99%
“…In addition, the formed spheroids pose challenges in immunostaining, imaging, retrieval, and storage. 16,17 Sodium alginate has been used as a biocompatible polymer material to support cell growth in 3D scaffolds. 18,19 Alginate scaffolds have demonstrated several advantages for 3D cell culture, including their ability to support cell growth and function and mimic many tissues' extracellular matrix (ECM).…”
Section: ■ Introductionmentioning
confidence: 99%